2018
DOI: 10.1002/pssb.201700653
|View full text |Cite
|
Sign up to set email alerts
|

Structural Stability, Electronic, and Optical Properties of BiVO4 With Oxygen Vacancy Under Pressure

Abstract: In this paper, first‐principles calculations are performed to investigate the elastic constants, structural stability, electronic properties, and optical properties of ideal BiVO4 and BiVO4 with oxygen vacancy (Vo‐BiVO4) under equivalent hydrostatic and z‐axial pressure. It is found that the structural stability of the material is not affected and the indirect band‐gap is well kept in BiVO4 and Vo‐BiVO4, independent of the applied pressure. Essentially, as the equivalent hydrostatic and z‐axial pressure is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Beyond this pressure, the most likely reason for explaining the decrease of the resistivity to detectable levels is the creation of oxygen vacancies which could act as donor levels, transferring electrons to the conduction band. The presence of such vacancies is typical of chromate compounds. Theoretical calculations on the related compound BiVO 4 have shown that the formation energy of oxygen vacancies can be provided by a hydrostatic pressure of 7 GPa . Therefore, it is not impossible to create oxygen vacancies in SrCrO 4 at 16 GPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond this pressure, the most likely reason for explaining the decrease of the resistivity to detectable levels is the creation of oxygen vacancies which could act as donor levels, transferring electrons to the conduction band. The presence of such vacancies is typical of chromate compounds. Theoretical calculations on the related compound BiVO 4 have shown that the formation energy of oxygen vacancies can be provided by a hydrostatic pressure of 7 GPa . Therefore, it is not impossible to create oxygen vacancies in SrCrO 4 at 16 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations on the related compound BiVO 4 have shown that the formation energy of oxygen vacancies can be provided by a hydrostatic pressure of 7 GPa. 55 Therefore, it is not impossible to create oxygen vacancies in SrCrO 4 at 16 GPa. These vacancies will act as donor impurities and provide n-type doping to SrCrO 4 , transforming it into an extrinsic semiconductor.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of an oxygen evolution catalyst, i.e., BiVO 4 abbreviated as “B” (monoclinic clinobisvanite phase) composed of tetrahedron and octahedron of VO 4 and BiO 8 , respectively, with threefold coordinated O, fourfold coordinated V, and eightfold coordinated Bi. This phase of B collects distinct attention in WORs as photoanode owing to its narrow bandgap of 2.3–2.5 eV, special crystal structure, electronic and optical properties, low cost, nontoxicity, layered structure, and favorable thermodynamic stability . However, the catalytic activity of B is retarded by some bottlenecks such as low charge separation and slow kinetics of WOR.…”
Section: Introductionmentioning
confidence: 99%
“…The orthorhombic Pca 2 1 symmetry defines nine independent C ij s: C 11 , C 12 , C 13 , C 22 , C 23 , C 33 , C 44 , C 55 , and C 66 that satisfy the required Born stability criterion C 11 > 0, C 44 > 0, C 55 > 0, C 66 > 0, C 11 C 22 > C 12 2 , C 11 C 22 C 33 + 2 C 12 C 13 C 23 − C 11 C 23 2 − C 22 C 13 2 − C 33 C 12 2 > 0,regardless of the vdW force as can be seen from Table S5†. 82–84 The salient elastic properties like bulk-modulus ( B V , B R and B H ), shear modulus ( G V , G R and G H ), Young's modulus ( E V , E R and E H ), Poisson's ratio ( ν V , ν R and ν H ) and Pugh's ratio ( k V , k R and k H ) were simulated for Voigt (V), Reuss (R) and Hill (H) framework. 85–87 The Hubbard ( U d , U p ) corrections and the vdW force inflate the bulk, shear, and Young's moduli compared to that of GGA-PBE which imply plastic deformation and stiffness enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…regardless of the vdW force as can be seen from Table S5 †. [82][83][84] The salient elastic properties like bulk-modulus (B V , B R and B H ), shear modulus (G V , G R and G H ), Young's modulus (E V , E R and E H ), Poisson's ratio (n V , n R and n H ) and Pugh's ratio (k V , k R and k H ) were simulated for Voigt (V), Reuss (R) and Hill (H) framework. [85][86][87] The Hubbard (U d , U p ) corrections and the vdW force inate the bulk, shear, and Young's moduli compared to that of GGA-PBE which imply plastic deformation and stiffness enhancement.…”
Section: Elastic Properties Simulationmentioning
confidence: 89%